Venous congestion assessment using point‐of‐care Doppler ultrasound: Welcome to the future of volume status assessment - Koratala, Abhilash (Clin Case Rep, 2021)
With evolution of clinician‐performed bedside ultrasonography, noninvasive markers of venous congestion such as hepatic, portal, and intrarenal venous Doppler waveforms are gaining importance as an adjunct to volume status assessment. The intent of this clinical image is to illustrate the classic sonographic stigmata of severe venous congestion, associated with worse prognosis.